OPTIMIZATION OF LIQUID SOAP SOAP (Caesalpinia sappan L.) LIQUID ETHANOL EXTRACT WITH KOH, STEARIC ACID AND SITRATE ACID USING SIMPLEX LATTICE DESIGN METHOD AND THE EFFECT OF ANTIBACTERIA ON STAPYLOCOCUSUSUSCATC 25259 - Nurhayati Nurul; Ana Indrayati; Mimiek Murrukmihadi (Universitas Duta Bangsa Surakarta, 2019)
The most widely used soap is soap from sodium salt, but potassium soap is a softer and more soluble soap in water, so potassium soap is made for special functions, such as liquid soap. Brazilin in secang wood extract (Caesalpinia sappan L.) has potential as an antioxidant and antibacterial agent. Secang wood dry powder was extracted with 96% ethanol, thickened and then extracts tested. Fourteen liquid soap formulas using 10% secang wood extract with variations of KOH base, stearic acid, and citric acid were tested for physical properties including viscosity, pH, and free alkali. The optimum formula liquid bath soap can inhibit S. aureus ATCC 25923 as large as 32.6 ± 0.75 mm. The optimum formula is obtained by the Simplex Lattice Design method, the results are analyzed by expert design software. The optimum formula was tested for physical properties then analyzed using one-sample t-test and irritation test. The optimum form of liquid bath extract of sabaun secang wood extract contains KOH 0.6121%, stearic acid 0.613% and citric acid 0.085% with physical properties of viscosity of 9.69, pH of 9.95 free alkali of 0.08. T test results showed no significant difference between the response of the physical properties of the experimental results and software predictions. The optimum formula for shower bath liquid wood extract does not irritate the skin.